Quantum Meruit and Building Contracts: Part II Does the Contract Price put a Ceiling on a Recovery via a Quantum Meruit? - HUNTER, Howard (Institutional Knowledge at Singapore Management University, 1989)
The question posed by the title of this part of the article has been the subject of a substantial amount of commentary by American legal scholars and has been a central issue in a number of cases, almost all of them involving building contracts. The problem is easy to state: P and D have an agreement for P to construct a building for a total consideration of $X. When P is partially finished, D breaches. If the contract price and the value of the work to date roughly coincide, there is usually little problem in determining P's recovery. The standard rule of measurement is: expenses incurred to date plus expected profit (the 'benefit of the bargain'). Difficulties arise when the value of P's work exceeds the contract price. We are thus concerned in this part with valid and enforceable contracts which have as their distinguishing feature, from the builder's perspective, an element of unprofitability.